Optimization of Machining Parameters on Tool Wear Rate of Ti-6Al-4V through EDM using Copper Tungsten Electrode A Statistical Approach - M. M., Rahman; M. M., Noor; K., Kadirgama; R. A., Bakar (2011)
Electrical discharge machining (EDM) is relatively modern machining process having distinct advantages over other machining processes and able to machine Ti-alloys effectively. This paper attempts to investigate the effects of peak ampere, pulse on time and pulse off time on tool wear rate (TWR) of titanium alloy Ti-6Al-4V in EDM utilizing copper tungsten as an electrode and positive polarity of the electrode. A mathematical model for electrode wear rate is developed in this paper. Design of experiments method and response surface methodology techniques are implemented. The validity test of the fit and adequacy of the proposed models has been carried out through analysis of variance. It can be seen that as the peak current increases the TWR decreases till certain ampere and then increases. The excellent surface finish is investigated in this study at short pulse on time and in contrast the long pulse duration causes the lowest TWR. Long pulse off time provides minimum TWR and the impact of pulse interval on TWR depends on peak current. The result leads to wear rate of electrode and economical industrial machining by optimizing the input parameters.